MECP2 Isoform-Specific Vectors with Regulated Expression for Rett Syndrome Gene Therapy - Rastegar, Mojgan (Public Library of Science, 2009)
BACKGROUND: Rett Syndrome (RTT) is an Autism Spectrum Disorder and the leading cause of mental retardation in females. RTT is caused by mutations in the Methyl CpG-Binding Protein-2 (MECP2) gene and has no treatment. Our objective is to develop viral vectors for MECP2 gene transfer into Neural Stem Cells (NSC) and neurons suitable for gene therapy of Rett Syndrome. METHODOLOGY/PRINCIPAL FINDINGS: We generated self-inactivating (SIN) retroviral vectors with the ubiquitous EF1α promoter avoiding known silencer elements to escape stem-cell-specific viral silencing. High efficiency NSC infection resulted in long-term EGFP expression in transduced NSC and after differentiation into neurons. Infection with Myc-tagged MECP2-isoform-specific (E1 and E2) vectors directed MeCP2 to heterochromatin of transduced NSC and neurons. In contrast, vectors with an internal mouse Mecp2 promoter (MeP) directed restricted expression only in neurons and glia and not NSC, recapitulating the endogenous expression pattern required to avoid detrimental consequences of MECP2 ectopic expression. In differentiated NSC from adult heterozygous Mecp2(tm1.1Bird)+/− female mice, 48% of neurons expressed endogenous MeCP2 due to random inactivation of the X-linked Mecp2 gene. Retroviral MECP2 transduction with EF1α and MeP vectors rescued expression in 95–100% of neurons resulting in increased dendrite branching function in vitro. Insulated MECP2 isoform-specific lentiviral vectors show long-term expression in NSC and their differentiated neuronal progeny, and directly infect dissociated murine cortical neurons with high efficiency. CONCLUSIONS/SIGNIFICANCE: MeP vectors recapitulate the endogenous expression pattern of MeCP2 in neurons and glia. They have utility to study MeCP2 isoform-specific functions in vitro, and are effective gene therapy vectors for rescuing dendritic maturation of neurons in an ex vivo model of RTT.